The Best Offense is Taking Out Cyber Proxies - Schuler Scott, Arianna; Kaminska, Monica (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.It has been interesting to see Russia goading other states on the cyber offensive front, acting through 'proxies', people recruited online to carry out illegal operations. To date no state has overtly condemned attacks that are undoubtedly rooted in the dark web, a space where criminals operate behind a veneer of anonymity and privacy. A mixture of technical and non-technical backgrounds, we are working to understand how to approach informed policy making in this area. Taking down an online anonymous marketplace (such as Alphabay, Hansa which was recently seized) does not seem to reduce illegal action, but disruption and the erosion of trust in the system might. By targeting prominent criminals and reducing demand, we hope to add weight to the recommendations we can make as researchers, and work with those in the defence industry to get things done.
Keywords: 'Dark web'; 'Cybercrime'; 'Human error'; 'DSDS17'; 'DSDS17 poster'; 'Information and Computing Sciences not elsewhere classified'